Internalisasi Nilai Islam dalam Pembentukan Karakter Pelajar pada Era Digital: Studi di SMPN 33 Bekasi - Ardiansyah Wowo (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2026)
Character education has become a strategic issue in the digital era, which is marked by the increasing complexity of moral challenges faced by adolescents. Schools, as formal educational institutions, play an important role in internalizing Islamic values as a foundation for students’ character development. This study aims to analyse the process of internalizing Islamic values and its implications for students’ character formation at SMPN 33 Bekasi City in responding to the dynamics of the digital era. This research employs a qualitative approach with a descriptive method. Data were collected through participatory observation, in-depth interviews with Islamic Religious Education teachers, guidance and counseling teachers, the school principal, and students, as well as document analysis of materials such as syllabi and lesson plans. The data were analysed using thematic analysis techniques through stages of data reduction, categorization, and reflective conclusion drawing. The findings indicate that the internalization of Islamic values is carried out through religious habituation practices (Qur’anic recitation, collective prayers, and congregational prayers), Rohis extracurricular activities, teachers’ role modeling, and the integration of Islamic values within classroom learning. This process is supported by strong school leadership commitment, collaboration among teachers across subject areas, and synergy between the school and families. The impact can be seen in the improvement of students’ discipline, responsibility, and ethical awareness in using social media. The study concludes that character education based on Islamic values becomes more effective when implemented through consistent habituation, exemplary conduct, and systemic integration within the school culture. The novelty of this research lies in the synthesis between Islamic values–based moral development and the strengthening of digital literacy within the context of a public school, thereby offering a model of character education that is more adaptive to the dynamics of the digital era.